2023
DOI: 10.3389/fendo.2023.1132194
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and single-cell transcriptome analyses of islet tissue unravel gene signatures associated with pyroptosis and immune infiltration in type 2 diabetes

Abstract: IntroductionType 2 diabetes (T2D) is a common chronic heterogeneous metabolic disorder. However, the roles of pyroptosis and infiltrating immune cells in islet dysfunction of patients with T2D have yet to be explored. In this study, we aimed to explore potential crucial genes and pathways associated with pyroptosis and immune infiltration in T2D.MethodsTo achieve this, we performed a conjoint analysis of three bulk RNA-seq datasets of islets to identify T2D-related differentially expressed genes (DEGs). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…Chronic oxidative stress can also leads to decreased responsiveness to insulin, ultimately leading to diabetes reported by Alina Berdichevsky et al (p=0.01) ( 169 ). Besides, NFKBIA affects the wound healing in diabetic foot ulceration (DFU) (p=0.006) ( 170 ), MYC and SCD are related to pyroptosis and immune infiltration in T2DM (p=0.001) ( 171 ). The experiment of Parker C. Wilson et al using single-nucleus RNA sequencing has been revealed that GCH1 is associated with early-stage diabetic nephropathy (p=4.88e-09) ( 172 ) In short, our results also presented key clinical indices with the help of the integrated oxidative model.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic oxidative stress can also leads to decreased responsiveness to insulin, ultimately leading to diabetes reported by Alina Berdichevsky et al (p=0.01) ( 169 ). Besides, NFKBIA affects the wound healing in diabetic foot ulceration (DFU) (p=0.006) ( 170 ), MYC and SCD are related to pyroptosis and immune infiltration in T2DM (p=0.001) ( 171 ). The experiment of Parker C. Wilson et al using single-nucleus RNA sequencing has been revealed that GCH1 is associated with early-stage diabetic nephropathy (p=4.88e-09) ( 172 ) In short, our results also presented key clinical indices with the help of the integrated oxidative model.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, the inhibition of NLRP3-mediated pyroptosis can effectively alleviate VCD. [31][32][33][34] Human NLRP1 was identified as the first sensor capable of forming inflammasomes and may play a key role in the progression of diabetes. A recent single-cell transcriptomic analysis of islet tissue in type 2 diabetes revealed that GSDMD, GSDMB, CASP1, and NLRP1 were significantly increased in diabetic patients.…”
Section: Significance Statementmentioning
confidence: 99%
“…Studies have reported that the inhibition of podocyte pyroptosis could induce a protective effect against renal injury in DN 30 . In addition, the inhibition of NLRP3‐mediated pyroptosis can effectively alleviate VCD 31–34 …”
Section: The Role Of Pyroptosis In Diabetes and Vcdmentioning
confidence: 99%
“…To date, the phenotypes and roles of T cells, NK cells, monocytes, macrophages and other immune cells have received less attention than other systems involved in diabetes mellitus [5][6]. In recent years, increasing evidence has shown that immune disorders are the main factors involved in the occurrence of T2DM [7][8][9]. Single-cell RNA sequencing (scRNA-seq) is a new technique that can be used to reveal cell heterogeneity and can be used to quantify the expression profile of each gene in each cell, which makes it easier to study genes.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the phenotypes and roles of T cells, NK cells, monocytes, macrophages and other immune cells have received less attention than other systems involved in diabetes mellitus [5][6]. In recent years, increasing evidence has shown that immune disorders are the main factors involved in the occurrence of T2DM [7][8][9]. Single-cell RNA .…”
Section: Introductionmentioning
confidence: 99%